Elastic plate osteosynthesis of femoral shaft fractures in young dogs - Cabassu, Jean-Pierre (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The outcome of femoral fracture repair in young growing dogs using the principle of elastic osteosynthesis was evaluated in a retrospective clinical trial. Unilateral fractures in twenty four dogs, in the first phase of their growth, were repaired with a Veterinary Cuttable Plate (VCP). The plates were applied according to the principles of bridge plating. They were fixed with two screws at each end, positioned as far as possible from the fracture site, leaving a flexible segment between them.The plates contained between seven and 20 holes. The dogs soon used their treated limb and callus was often complete by four weeks. The plates were removed in 18 cases. A very good outcome was recorded in 21 dogs, one dog ran away after two months at which time the owner reported an excellent gait, one dog died of an unrelated problem and one other dog exhibited slight lameness which was attributed to stifle problems. In all of the cases the growing diaphysis was apparently undisturbed. It was concluded that adequate fixation of the fractures was achieved and conditions for rapid bone union was created.The successful use of Veterinary Cuttable Plates, VCP, for the treatment of fractured femurs in immature dogs, is reported
Keywords: Canine; femoral fracture; elastic osteosynthesis